2015
DOI: 10.1002/ange.201504790
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Salts of Anionic Chiral Cobalt(III) Complexes as Catalysts of the Enantioselective Povarov Reaction

Abstract: The sodium salts of anionic chiral cobalt(III) complexes (CCC À Na + )h ave been found to be efficient catalysts of the asymmetric Povarov reaction of easily accessible dienophiles,s uch as 2,3-dihydrofuran, ethyl vinyl ether, and an N-protected 2,3-dihydropyrrole,w ith 2-azadienes. Ring-fused tetrahydroquinolines with up to three contiguous stereogenic centers were thus obtained in high yields,excellent diastereoselectivities (endo/exo up to > 20:1), and high enantioselectivities (up to 95:5 e.r.).The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The use of a 2-nitro phenyl aromatic imine 75 in the reaction favored formation of the endo-product 74b ( Table 2 , Entry 2). The endo-compound 74c was also obtained from the zinc triflate catalyzed Povarov reaction conducted by Wang and co-workers ( Table 2 , Entry 3) [ 59 ], as well as from the cobalt catalyzed reaction employing catalyst 76, presented by Gong and co-workers ( Table 2 , Entry 4) [ 60 ]. Other catalysts that have been explored for this reaction are the iodo catalyst 77 ( Table 2 , Entry 5) and helquat catalyst 78 ( Table 2 , Entry 6), both of which facilitated formation of approximately 1:1 mixtures of endo/exo isomers [ 61 , 62 ].…”
Section: Tricyclic Core Scaffold Synthesismentioning
confidence: 99%
“…The use of a 2-nitro phenyl aromatic imine 75 in the reaction favored formation of the endo-product 74b ( Table 2 , Entry 2). The endo-compound 74c was also obtained from the zinc triflate catalyzed Povarov reaction conducted by Wang and co-workers ( Table 2 , Entry 3) [ 59 ], as well as from the cobalt catalyzed reaction employing catalyst 76, presented by Gong and co-workers ( Table 2 , Entry 4) [ 60 ]. Other catalysts that have been explored for this reaction are the iodo catalyst 77 ( Table 2 , Entry 5) and helquat catalyst 78 ( Table 2 , Entry 6), both of which facilitated formation of approximately 1:1 mixtures of endo/exo isomers [ 61 , 62 ].…”
Section: Tricyclic Core Scaffold Synthesismentioning
confidence: 99%
“…[7] This feature is distinct from the traditional metal complexes wherein the positive charge on the metal is compensated by ligand coordination and thus would be able to make either the acid or salt form of anionic chiral metal complexes hold unique privilege in asymmetric catalysis.T herefore,t he creation of as tructurally diverse range of new chiral metal complexes and disinterment of their applications in asymmetric catalysis would be essentially important in synthetic organic chemistry.H erein, we describe the L-a nd Ddiastereomeric cobalt(III) complexes which act as "pseudoenantiomers" which render asymmetric reactions to give both enantiomers,a nd demonstrate the versatility of the chiral cobalt(III)-templated Brønsted acids as highly efficient catalysts for asymmetric bromoaminocyclization of olefins (Scheme 1). [7] This feature is distinct from the traditional metal complexes wherein the positive charge on the metal is compensated by ligand coordination and thus would be able to make either the acid or salt form of anionic chiral metal complexes hold unique privilege in asymmetric catalysis.T herefore,t he creation of as tructurally diverse range of new chiral metal complexes and disinterment of their applications in asymmetric catalysis would be essentially important in synthetic organic chemistry.H erein, we describe the L-a nd Ddiastereomeric cobalt(III) complexes which act as "pseudoenantiomers" which render asymmetric reactions to give both enantiomers,a nd demonstrate the versatility of the chiral cobalt(III)-templated Brønsted acids as highly efficient catalysts for asymmetric bromoaminocyclization of olefins (Scheme 1).…”
mentioning
confidence: 99%
“…[5] In addition, in the cases concerning chiral metal complexes (Ru II ,C o III )w ith chiral ligands, [4,6] the nature of asymmetric induction has not been identified for the moment.We recently demonstrated that sodium salts of anionic chiral cobalt(III) complexes (Scheme 1, L-1c)were excellent catalysts for the asymmetric Povarov reaction of simple 2azadienes,a nd the weakly bonding nature of chiral ion-pair was believed to permit the alkali cation to work as aL ewis acid for the activation of imine functionality. [7] This feature is distinct from the traditional metal complexes wherein the positive charge on the metal is compensated by ligand coordination and thus would be able to make either the acid or salt form of anionic chiral metal complexes hold unique privilege in asymmetric catalysis.T herefore,t he creation of as tructurally diverse range of new chiral metal complexes and disinterment of their applications in asymmetric catalysis would be essentially important in synthetic organic chemistry.H erein, we describe the L-a nd Ddiastereomeric cobalt(III) complexes which act as "pseudoenantiomers" which render asymmetric reactions to give both enantiomers,a nd demonstrate the versatility of the chiral cobalt(III)-templated Brønsted acids as highly efficient catalysts for asymmetric bromoaminocyclization of olefins (Scheme 1).After the diastereoselective synthesis of sodium salts and Brønsted acids of anionic chiral cobalt(III) complexes was achieved, [8] we chose bromoaminocyclization of olefins as ab enchmark reaction, [9,10] which has received increasing interest as the corresponding products (e.g., pyrrolidines) are core structural elements in pharmaceuticals and organocatalysts, [11] and thereby are of high synthetic significance.T he reaction of the g-amino alkene 2a with N-bromosuccinimide (NBS) was initially examined in the presence of 5mol %o f the sodium salts of anionic chiral cobalt(III) complexes, L-(S,S)-1a-c (Table 1). As anticipated, the desired reaction proceeded smoothly to give the 2-substituted pyrrolidine 3a in good yields,b ut with low levels of enantioselectivity (entries 1-3).…”
mentioning
confidence: 99%
See 1 more Smart Citation